Analisis Nilai Kapasitansi Komposit Lithium Besi Oksida (Li5FeO4) dan Karbon Aktif Kulit Biji Mete sebagai Bahan Dasar Elektroda Baterai Lithium: Efek Variasi Massa - Ahmad, Ahmad; Erniwati, Erniwati; RM, Vivi Hastuti (Jurusan Pendidikan Fisika, 2020)
Previous researchers have investigated the manufacture of lithium battery electrode materials from Li5FeO4 composites with activated carbon of cashew nutshells. However, the effect of combining activated carbon to the lithium battery electrode material was not reviewed. The purpose of this study was to determine the effect of the comparison of the mass composition of Li5FeO4 and cashew nut shell active carbon on the capacitance value of the lithium battery electrode. These electrodes generated using the high-temperature solid-state method. The material used is iron oxide Fe2O3 from iron sand and LiOH.H2O, which homogenized with a sintering temperature of 850ÌŠC for 15 hours with a ratio of 6/1 to produce Li5FeO4. Then Li5FeO4 was compiled with activated carbon of cashew nut shells with a mass fraction of activated carbon 60%, 50%, 40%, and 20%. Furthermore, it characterized using cyclic voltammetry. The results of cyclic voltammetry characterization for a mass fraction of 60% produce a capacitance of 4.7 F / g, a mass fraction of 50% produces a capacitance of 59.1 F / g, a mass fraction of 40% produces a capacitance of 87, 3 F / g, and a mass fraction of 20% produces capacitance of 243 F / g. From the four variations of mass fraction, the capacitance that meets the lithium battery electrode capacitance on the market is the mass fraction of 20%.